2019
DOI: 10.1016/j.apmr.2018.04.031
|View full text |Cite
|
Sign up to set email alerts
|

Does Therapy With Biofeedback Improve Swallowing in Adults With Dysphagia? A Systematic Review and Meta-Analysis

Abstract: Dysphagia therapy augmented by biofeedback using sEMG and accelerometry enhances hyoid displacement but functional improvements in swallowing are not evident. However, data are extremely limited and further larger well-designed RCTs are warranted.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
52
0
9

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(62 citation statements)
references
References 56 publications
1
52
0
9
Order By: Relevance
“…For five conditions (fecal incontinence, 12 urinary incontinence in women, 13 dysphagia, 14 stroke, 15 and Bell's palsy 16 ), systematic reviews specifically examined biofeedback as an adjunct to another intervention. Five reviews examined the effectiveness of biofeedback for conditions (sleep bruxism, 17 chronic idiopathic constipation, 18 knee osteoarthritis, 10 balance/gait training, 19 and intradialytic hypotension 20 ) independent of other interventions.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For five conditions (fecal incontinence, 12 urinary incontinence in women, 13 dysphagia, 14 stroke, 15 and Bell's palsy 16 ), systematic reviews specifically examined biofeedback as an adjunct to another intervention. Five reviews examined the effectiveness of biofeedback for conditions (sleep bruxism, 17 chronic idiopathic constipation, 18 knee osteoarthritis, 10 balance/gait training, 19 and intradialytic hypotension 20 ) independent of other interventions.…”
Section: Resultsmentioning
confidence: 99%
“…2 and Table 3). 19 It is unclear whether biofeedback is effective for the treatment of Bell's palsy, 16 chronic idiopathic constipation, 18 dysphagia, 14 osteoarthritis of the knee, 10 labor pain, 24 Raynaud's, 26 and sleep bruxism. 17 Limited (low-confidence) evidence suggests that biofeedback provides no benefit for urinary incontinence in women once differences in PFMT programs were controlled for, 13 nor was it effective for blood pressure control.…”
Section: Resultsmentioning
confidence: 99%
“…In this way, the training accuracy is maintained. Although there is no sufficient evidence that biofeedback benefits overall swallowing functions among patients with dysphagia, in studies that used tongue manometry as biofeedback, significant increases in maximum isometric and swallowing tongue pressure were observed in patients who received biofeedback compared with those who did not [ 69 ]. In addition, a previous study has suggested that home-based therapy can be as effective as office-based therapy if a biofeedback system is applied [ 70 ].…”
Section: Discussionmentioning
confidence: 99%
“…The most common biofeedback technique used in post-stroke dysphagia therapy is surface electromyography (sEMG). sEMG biofeedback uses two small electrodes placed on the submental muscles to measure the timing and force of the muscle contraction, which is displayed graphically on a screen [ 88 , 89 ]. A recent meta-analysis found that sEMG biofeedback coupled with swallowing maneuvers increased hyoid displacement in post-stroke dysphagia patients when compared with controls [ 88 ].…”
Section: How Can We Improve Treatment Of Post-stroke Dysphagia?mentioning
confidence: 99%
“…sEMG biofeedback uses two small electrodes placed on the submental muscles to measure the timing and force of the muscle contraction, which is displayed graphically on a screen [ 88 , 89 ]. A recent meta-analysis found that sEMG biofeedback coupled with swallowing maneuvers increased hyoid displacement in post-stroke dysphagia patients when compared with controls [ 88 ]. sEMG biofeedback has the potential for short-term benefits to dysphagia rehabilitation; however, it has been hypothesized that once patients learn swallowing therapies, biofeedback yields no further benefits.…”
Section: How Can We Improve Treatment Of Post-stroke Dysphagia?mentioning
confidence: 99%